THE EFFECT OF SERVICE QUALITY AND COMPANY IMAGE ON CUSTOMER SATISFACTION AT NEW HOLLYWOOD HOTEL PEKANBARU - Lisnarita, Reska Jan Anggraini; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of service quality and company image on customer satisfaction at New Hollywood Hotel Pekanbaru. Service quality as variable (X1) company image as variable (X2) and customer satisfaction as (Y).The method in this research is descriptive and quantitative by using SPSS program, where the sample used is guest who stay more than 2 times in New Hollywood Hotel Pekanbaru with 100 respondents. To determine the amount of sampel, slovin formula was used with accidental sampling technique. Data collection techniques through questionnaires and interviews.The result of analysis use multiple linear regression, t test, and f test so that it can be seen that service variable had significantly effect on customer satisfaction and the company image also had a significant effect on customer satisfaction, and service quality and company image simultaneously had significant effect on customer satisfaction.  Keywords: Service Quality, Company Image, Customer Satisfaction